Pazuzu or the Pentagon: Who’s the Real Demon? - Downey, Jack Lee (The journal of gods and monsters, 2025)
In February 1981, a teenage landscaper named Arne Johnson murdered his landlord Alan Bono, following a family lunch at the Mug ‘N’ Munch pub in Brookfield, Connecticut. The case was destined to be a generic senseless episode of suburban violence, but for Johnson’s highly irregular defense plea: that this was all due to a case of demonic possession. The sensational allegation quickly gained national attention, as more details of the possession came to light, including the investigative services of the clairvoyant-demonologist couple Lorraine and Ed Warren. This essay will recount the story of the Bono murder and an exorcist priest whose mother was called into jury duty for the case, as a means of reflecting on this era of clerical charisma in the American popular imagination.